Neither Here Nor There - Al Hasan, Hasan (Lebanon : Arab Resource Center for Popular Arts, 2007)
Many Palestinian youth believe that immigration is the best solution for economic and social problems they face. This film explores the experiences of some young Palestininas who tried to reach the dream of immigration. This film is the result of a cooperation between a team of young refugees who participated in preparing, shooting and editing.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films